Effectiveness of Human Papillomavirus (HPV) Vaccination Against Penile HPV Infection in Men Who Have Sex With Men and Transgender Women. (28th July 2021) - Winer, Rachel L; Lin, John; Querec, Troy D; Unger, Elizabeth R; Stern, Joshua E; Rudd, Jessica M; Golden, Matthew R; Swanson, Fred; Markowitz, Lauri E; Meites, Elissa
Abstract: Background: In the United States, human papillomavirus (HPV) vaccination has been recommended since 2011 for boys aged 11–12 years, with catch-up vaccination recommended through age 26 years for previously unvaccinated men who have sex with men (MSM). Methods: During 2016–2018, a cross-sectional study enrolled MSM and transgender women aged 18–26 years in Seattle, Washington. Participants submitted self-collected penile swab specimens for HPV genotyping. HPV vaccination history was self-reported. We compared HPV prevalence among vaccinated participants with that in participants with no or unknown vaccination history, using log-binomial regression to estimate adjusted prevalence ratios and confidence intervals. Results: Among 687 participants, 348 (50.7%) self-reported ever receiving ≥1 HPV vaccine dose; the median age at first HPV vaccination was 21 years, and the median age at first sex, 17 years. Overall, the prevalence of penile quadrivalent HPV vaccine (4vHPV)–type HPV was similar in vaccinated participants (12.1%) and participants with no or unknown vaccination (15.6%) (adjusted prevalence ratio, 0.69 [95% confidence interval, .47–1.01]). However, the prevalence was significantly lower in participants vaccinated at age ≤18 years than in those with no of unknown vaccination (0.15 [.04–.62]), corresponding to a vaccine effectiveness of 85% against 4vHPV-type HPV. Conclusions: Results suggest that HPV vaccination is effective in preventing penile HPV infections in young MSM when administered at age ≤18 years. Abstract : Penile quadrivalent human papillomavirus (HPV) vaccine–type HPV prevalence was lower among young men who have sex with men (MSM) self-reporting HPV vaccination at age ≤18 years than among MSM with no or unknown vaccination. Results suggest that HPV vaccination is effective against penile HPV infections when administered to MSM aged ≤18 years.